2020
DOI: 10.15252/msb.20209596
|View full text |Cite
|
Sign up to set email alerts
|

Reduced proteasome activity in the aging brain results in ribosome stoichiometry loss and aggregation

Abstract: A progressive loss of protein homeostasis is characteristic of aging and a driver of neurodegeneration. To investigate this process quantitatively, we characterized proteome dynamics during brain aging in the short-lived vertebrate Nothobranchius furzeri combining transcriptomics and proteomics. We detected a progressive reduction in the correlation between protein and mRNA, mainly due to posttranscriptional mechanisms that account for over 40% of the ageregulated proteins. These changes cause a progressive lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
122
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(160 citation statements)
references
References 93 publications
(133 reference statements)
15
122
3
Order By: Relevance
“…Conversely, an intact proteasome is correlated with extreme longevity in humans ( Chondrogianni et al, 2000 ), while proteasome activation can increase cellular and organismal lifespan, alleviate aggregation-related pathologies and enhance stemness ( Chondrogianni et al, 2000 ; Kapeta et al, 2010 ; Chondrogianni et al, 2015a ; Kapetanou et al, 2017 ). Interestingly, studies in brain have demonstrated the link between proteasome activity and aging ( Triplett et al, 2015 ; Kelmer Sacramento et al, 2020 ), while Tropea and co-workers have proposed the involvement of IIS in these processes ( Wrigley et al, 2017 ). Other studies on skeletal muscle atrophy have addressed the role of mammalian FoxOs in the positive regulation of ubiquitin ligases.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, an intact proteasome is correlated with extreme longevity in humans ( Chondrogianni et al, 2000 ), while proteasome activation can increase cellular and organismal lifespan, alleviate aggregation-related pathologies and enhance stemness ( Chondrogianni et al, 2000 ; Kapeta et al, 2010 ; Chondrogianni et al, 2015a ; Kapetanou et al, 2017 ). Interestingly, studies in brain have demonstrated the link between proteasome activity and aging ( Triplett et al, 2015 ; Kelmer Sacramento et al, 2020 ), while Tropea and co-workers have proposed the involvement of IIS in these processes ( Wrigley et al, 2017 ). Other studies on skeletal muscle atrophy have addressed the role of mammalian FoxOs in the positive regulation of ubiquitin ligases.…”
Section: Discussionmentioning
confidence: 99%
“…To obtain more direct evidence for protein remodeling of ribosomes, one should directly measure RP abundances as a more direct approach for evaluating ribosome remodeling across different conditions, Figure 1a. Such analyses in cell lysates have suggested changes in the protein composition of ribosomes as budding yeast undergoes the diauxic shift, [55] during aging, [56,57] and upon LPS-stimulation of mouse dendritic cells. [58] In addition, RP analysis from cell lysates has shown that ribosomal transcripts exhibit slower elongation rates with decreased protein production relative to other transcripts with similar ribosome densities.…”
Section: Post-transcriptional Regulation Of Ribosomal Proteinsmentioning
confidence: 99%
“…3 d) [ 22 , 23 ], regeneration [ 24 ], neurodegeneration [ 25 ], and heart and muscle biology [ 26 , 27 ]. At the molecular level, studies have focused on mitochondrial function [ 28 ], epigenetics [ 26 , 29 ], telomere attrition [ 30 ], lipid peroxidation [ 31 ], and expression changes at the genome-wide and proteome-wide levels [ 26 , 29 , 32 38 ]. These phenotypes are conserved to a significant degree between humans and N. furzeri [ 29 , 39 ] .…”
Section: Major Interests and Research Questionsmentioning
confidence: 99%
“…Nothobranchius fishes are convenient experimental models for life-long investigations on the effects of dietary and environmental manipulations. They are particularly suited to study the effects of compounds that can be administered via injections [ 38 ], with the food [ 40 ] or in the water [ 37 ] in the context of pharmacology or ecotoxicology. Similarly, long-term consequences of exposure to environmental toxins can be investigated.…”
Section: Experimental Approachesmentioning
confidence: 99%